Differential Biological Effects of Dietary Lipids and Irradiation on the Aorta, Aortic Valve, and the Mitral Valve - Donis, Nathalie; Jiang, Zheshen; D'Emal, Céline; Hulin, Alexia; Debuisson, Margaux; Dulgheru, Raluca; Nguyen, Mai-Linh; Postolache, Adriana; Lallemand, François; Coucke, Philippe; Martinive, Philippe; Herzog, Marielle; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims Dietary cholesterol and palmitic acid are risk factors for cardiovascular diseases (CVDs) affecting the arteries and the heart valves. The ionizing radiation that is frequently used as an anticancer treatment promotes CVD. The specific pathophysiology of these distinct disease manifestations is poorly understood. We, therefore, studied the biological effects of these dietary lipids and their cardiac irradiation on the arteries and the heart valves in the rabbit models of CVD. Methods and Results Cholesterol-enriched diet led to the thickening of the aortic wall and the aortic valve leaflets, immune cell infiltration in the aorta, mitral and aortic valves, as well as aortic valve calcification. Numerous cells expressing α-smooth muscle actin were detected in both the mitral and aortic valves. Lard-enriched diet induced massive aorta and aortic valve calcification, with no detectable immune cell infiltration. The addition of cardiac irradiation to the cholesterol diet yielded more calcification and more immune cell infiltrates in the atheroma and the aortic valve than cholesterol alone. RNA sequencing (RNAseq) analyses of aorta and heart valves revealed that a cholesterol-enriched diet mainly triggered inflammation-related biological processes in the aorta, aortic and mitral valves, which was further enhanced by cardiac irradiation. Lard-enriched diet rather affected calcification- and muscle-related processes in the aorta and aortic valve, respectively. Neutrophil count and systemic levels of platelet factor 4 and ent-8-iso-15(S)-PGF2α were identified as early biomarkers of cholesterol-induced tissue alterations, while cardiac irradiation resulted in elevated levels of circulating nucleosomes. Conclusion Dietary cholesterol, palmitic acid, and cardiac irradiation combined with a cholesterol-rich diet led to the development of distinct vascular and valvular lesions and changes in the circulating biomarkers. Hence, our study highlights unprecedented specificities related to common risk factors that underlie CVD.